SBA-15-supported ultrastable Mo2N@CN catalysts for hydrodeoxygenation of guaiacol. (January 2023) - Wang, Fan; Wen, Chenglong; Lu, Mohong; Zhang, Peng; Zhu, Jie; Li, Mingshi; Shan, Yuhua; Song, Chunshan
Abstract: Mo2 N@NC/SBA-15 with high stability and dispersion were prepared by employing MoCl5 and dicyandiamide as Mo and C/N sources, respectively. Mo2 N was in situ formed while dicyandiamide was converted to N-doped carbon (NC) during the carbonization process under H2 at an elevated temperature. The generation of ultrafine Mo2 N nanoparticles (NPs) is attributed to N-doped carbon species around Mo2 N NPs, which prevents the aggregation of Mo2 N NPs at high carbonization temperature. Mo2 N@NC/SBA-15 catalysts exhibit high hydrodeoxygenation activity and aromatic compound selectivity. Product distribution is heavily influenced by the conditions under which the reactions occur. High pressure and elevated temperature are optimal for the formation of aromatic products. At 380 °C and 2 MPa, the selectivity to aromatic products reached up to 92%, with the guaiacol conversion reaching 99%. Highlights: Mo2 N@NC/SBA-15 was prepared by using MoCl5 and dicyandiamide as Mo and C/N source. Mo2 N@NC/SBA-15 has high stability and Mo2 N dispersion. Mo2 N@NC/SBA-15 shows high HDO activity and high selectivity to aromatic compounds. High pressure and elevated temperature favor formation of arene over Mo2 N@NC/SBA-15.